Digital Mental Health: Definitions, Concepts and Dimensions– A Scoping Review - Bagheri Hoseinabadi, Fatemeh; Fallahchai, Reza; Salehi, Keyvan; Samavi, Abdolvahab (Journal of Foresight and Health Governance, 2026)
Digital mental health (DMH) interventions, powered by artificial intelligence, mobile applications, and telemedicine, are rapidly advancing. These developments are transforming mental health care delivery, particularly in the context of global clinician shortages and the persistent impacts of the COVID-19 pandemic. However, the field lacks unified conceptual foundations, hindering standardization and equitable implementation. Following PRISMA-ScR guidelines, this scoping review synthesizes definitions of DMH from 33 peer-reviewed articles (2020–2025), identifies core dimensions and indicators, and evaluates existing assessment frameworks. Systematic searches across PubMed, PsycINFO, Scopus, and Web of Science revealed an evolution from broad technology-enabled support to sophisticated, AI-driven models that emphasize personalization, predictive analytics, and real-time adaptation. The review identified twelve core dimensions—including accessibility, equity and inclusion, co-design, effectiveness, engagement, usability, data privacy, implementation, youth involvement, cultural relevance, and refugee-specific considerations—with frequently reported indicators such as adherence, retention, user satisfaction, and symptom reduction. Evaluated frameworks (e.g., APA App Evaluation Model, NASSS, Digital Therapeutic Alliance, and E-XAI) demonstrated theoretical adaptability but highlighted significant resource and implementation barriers. We propose a comprehensive, integrative definition of DMH informed by the synthesized evidence. This scoping review underscores the transformative potential of DMH to deliver scalable, personalized, and equitable care worldwide, while persistent gaps in conceptual consensus, privacy policies, and culturally sensitive evaluation tools remain critical challenges. These findings highlight the urgent need for global terminological agreement and robust assessment standards to ensure DMH becomes truly inclusive and sustainable for diverse and underserved populations.